Invisible city: a Jerusalem in the forest?. Issue 4 (19th May 2018) - Steane, Mary Ann
Abstract : The Bielski partisans are perhaps the most famous of the 'Forest Jews' of Belarus, Jews who engaged in active resistance to the Germans in the years between 1941 and 1944 from their hide-outs in the forest. When they escaped to 'partisan country' Jews had to adjust to an entirely new physical and social environment. Persecuted by one of the most technologically advanced armies in the world, and forced by circumstances to join the Soviet-led, communist, anti-religious partisan movement, the Bielski group faced numerous social and cultural dilemmas in establishing the living conditions that ensured their survival. The extreme cold of the Russian winter made circumstances extremely harsh, 'living like animals' according to one partisan, although in time life improved sufficiently for many in the Bielski detachment to believe that their final camp had acquired the status of a small town or shtetl . If, however, such military camps have often recalled more established urban settlements, this question requires clarification in the Bielski case, and is the principal focus of this paper. In its examination of the dwellings and settlements constructed by the Bielski group, and how they evolved over time, the study underlines the minimum dimensions of culture that arise in near-survival conditions.